OBOR: what, why, how and implications - Hossain, Ishtiaq (2017)
China’s announcement of “One Belt, One Road” initiative has attracted much attention from policy-makers and think tanks in Asia and elsewhere •In this paper, we aim to explain the following: •1.the man features of such an initiative; •2. explain the main reasons for China to launch such a policy initiative ; and •3. its potential implications.